"Effect of Critical Thinking Skill on Mathematics Performance of Senior Secondary School Students in Ibadan, Nigeria." (2016)
"This study investigated the effect of Critical Thinking Skill on Mathematics performance of senior secondary school students, Ibadan. This study adopted the pre-test post test control group quasiexperimental design with 2x2 factorial matrix. Two schools were selected randomly from two different local government area in Ibadan and sixty senior secondary school students were used for the study. The major instrument used for the study was Mathematics Performance Test. The data were analysed using Analysis of Covariance tested at 0.05 level of significance. The results showed a significant main effect of . treatment of Mathematics performance among participants. Also, Critical Thinking Skill was more effective than Control group. Furthermore, it was found that there was significant main effect of gender in enhancing Mathematics performance of students. At the end, intervention programme was found effective means of enhancing students' understanding of Mathematics concepts. It is therefore recommended that students should be encouraged through different intervention in learning mathematic and to reduce examination anxiety."